Le regard des formés sur les compétences transversales : outils de connaissance et de re-connaissance - Sabrina Labbé; Naïma Marengo; Loïc Gojard; Sylvie Bourlot-Ranty (Nantes Université, 2019)
The notion of transferable skills appears as a major issue in the safeguarding of curricula and is key to adaptability on the labour market. We can therefore imagine why they are particularly valued in professional certifications. Our study explores this notion by investigating students in a university program built around the development of transferable skills that was, paradoxically, recently suppressed from the french National Register of Professional Certifications (RNCP). In such a context, what are the students' representations of the skills acquired in their course? And how do they express and share them? We examine the difficulty of the process of enunciating university trainings in terms of skills, the identity function of skills oscillating between being a knowledge tool and a recognition tool, and the necessary taking into account of the contexts in which skills are made explicit and, finally, we look at how hermetic the barrier between transferable and specific skills is.